The short-run macroeconomic impact of foreign aid to small states: An agnostic timeseries analysis - Henrik Hansen; Derek Headey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This study econometrically evaluates the short-run impact of aid in small developing countries (SDCs) by applying a VAR model to study aid's impact on 'absorption' (increasing import demand) and 'spending' (increased domestic demand) across countries. Whilst our approach allows parameters to vary across countries, the focus is on average country effects and differential effects within certain subgroups of countries. In particular, we find substantial differences between 'aid-dependent' SDCs and other SDCs which are more dependent on mineral resources and financial services. In the latter group, aid seems to be neither absorbed nor spent in any systematic fashion. But in the aid-dependent SDCs, aid receipts seem to be used more in the textbook 'absorb and spend' fashion.
Keywords: O11; O23; C53; 330; foreign aid; small developing countries; macroeconomic adjustment; absorption; spending; VAR models; panel data; Entwicklungshilfe; Makroökonomischer Einfluss; VAR-Modell; Entwicklungsländer; Kleines-Land-Modell